2002
DOI: 10.7326/0003-4819-137-5_part_1-200209030-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian National Breast Screening Study-1: Breast Cancer Mortality after 11 to 16 Years of Follow-up: A Randomized Screening Trial of Mammography in Women Age 40 to 49 Years

Abstract: After 11 to 16 years of follow-up, four or five annual screenings with mammography, breast physical examination, and breast self-examination had not reduced breast cancer mortality compared with usual community care after a single breast physical examination and instruction on breast self-examination. The study data show that true effects of 20% or greater are unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
1
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(255 citation statements)
references
References 21 publications
7
227
1
20
Order By: Relevance
“…[2][3][4] Furthermore, Otto et al 5,6 showed that the Dutch population-based screening programme is effective in reducing breast cancer mortality. The evidence for the benefit of mammography screening for younger women is less conclusive, [7][8][9] however, an effect for this age group is supported by several studies. Although the UK Age Trial showed a non-significant 17% reduction in breast cancer mortality, 9 a statistically significant breast cancer mortality reduction of 15% to 18% associated with screening for women aged 39 to 49 or 40 to 49 at entry was demonstrated by several meta-analyses of randomised controlled trials.…”
mentioning
confidence: 99%
“…[2][3][4] Furthermore, Otto et al 5,6 showed that the Dutch population-based screening programme is effective in reducing breast cancer mortality. The evidence for the benefit of mammography screening for younger women is less conclusive, [7][8][9] however, an effect for this age group is supported by several studies. Although the UK Age Trial showed a non-significant 17% reduction in breast cancer mortality, 9 a statistically significant breast cancer mortality reduction of 15% to 18% associated with screening for women aged 39 to 49 or 40 to 49 at entry was demonstrated by several meta-analyses of randomised controlled trials.…”
mentioning
confidence: 99%
“…The Canadian NBSS1 trial, which was designed to compare the effect of screening by mammography and physical examination with an initial physical examination only in women aged 40 -49 at entry, has suffered from low statistical power, and has also been criticised for the use of a volunteer population and doubts about the quality of mammography. After 11 -16 years of follow-up, this trial has shown no difference in breast cancer mortality between the two arms (Miller et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…The reductions in breast cancer mortality varied from 20% in the Marmot report12 to 32% from the Two County Study 13. This reflected that the Marmot report used all RCTs, including the two Canadian outliers,15, 16 and that the Two County Study was the single RCT with the largest reduction in breast cancer mortality. The proportion of overdiagnosed cases varied from 2.3% in the Danish data to 15.6% in the Norwegian data.…”
Section: Discussionmentioning
confidence: 99%